2007
DOI: 10.1080/07366290701634578
|View full text |Cite
|
Sign up to set email alerts
|

Development of a TODGA based Process for Partitioning of Actinides from a PUREX Raffinate Part I: Batch Extraction Optimization Studies and Stability Tests

Abstract: The extractant, N,N,N 0 ,N 0 -tetraoctyl diglycolamide (TODGA) has been evaluated for the separation of actinides(III) and lanthanides(III) from a high active raffinate (HAR). The effect of oxalic acid and HEDTA complexant on the extraction of actinides(III), lanthanides(III), and important fission products (e.g. Mo, Pd, Sr, Zr, Ru etc.) from synthetic HAR has been studied with 0.2 mol/L TODGA in TPH.With an extractant mixture of TODGA and tributyl phosphate (TBP) the amount of oxalic acid can be reduced to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(151 citation statements)
references
References 20 publications
9
136
0
1
Order By: Relevance
“…Following this, Modolo et al optimized the partitioning process and suggested a new continuous process in which the extractant was a mixture of 0.2 mol/L TODGA and 0.5 mol/L TBP in TPH [28]. The addition of TBP not only improved the hydrodynamic properties but also increased the loading capacity of the extractant and reduced the tendency to third-phase formation.…”
Section: An(iii) + Ln(iii) Co-extraction Using Todga-based Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this, Modolo et al optimized the partitioning process and suggested a new continuous process in which the extractant was a mixture of 0.2 mol/L TODGA and 0.5 mol/L TBP in TPH [28]. The addition of TBP not only improved the hydrodynamic properties but also increased the loading capacity of the extractant and reduced the tendency to third-phase formation.…”
Section: An(iii) + Ln(iii) Co-extraction Using Todga-based Solventsmentioning
confidence: 99%
“…using TODGA (Fig. 3) as extracting agent [23,28,29]. A hydrophilic complexing agent selective for An(III) over Ln(III) such as DTPA (diethylenetriaminepentaacetic acid) is used for back-extracting An(III) from the loaded organic phase.…”
Section: Innovative-sanexmentioning
confidence: 99%
“…N,N-dimethyl-N,N-dioctylhexylethoxymalonamide (DMDOHEMA) has become the reference molecule for the DIAMEX processs [13,14] enhancing the extractive properties towards trivalent elements and shortening the degradation compounds formed by acidic hydrolysis and radiolysis [15]. Recently, a new process for recovery of trivalent actinides from PUREX-type raffinate utilizing N,N,N,N--tetraoctyldiglycolamide (TODGA) was developed [16][17][18][19][20][21][22]. In a fi rst step a very effi cient extraction of An(III) and Ln(III) from acidic medium is performed, followed by their stripping using diluted nitric acid [19].…”
Section: Reprocessability Of Molybdenum and Magnesia Based Inert Matrmentioning
confidence: 99%
“…To facilitate this, a rotating diffusion cell (RDC) [4] apparatus has been established to enable the study of coupled interfacial-mass transfer kinetics of several organic extractant molecules which are to be studied including TBP, TODGA [5,6], CyMe 4 -BTBP [7] and CyMe 4 -BTPhen [8]. The RDC is derived from the Lewis cell but whereas the Lewis design comprises two directly interfaced liquid phases within a single container and utilizes individual stirrers within each phase to generate interfacial fl ux, the RDC includes two separate compartments into which the two solution phases are placed.…”
Section: Introductionmentioning
confidence: 99%